The Effectiveness of Jigsaw Technique in Teaching Passive Voice - Syofian Hadi (Journal Corner of Education, Linguistics, and Literature, 2023)
The objective of this research was to find out whether jigsaw technique is effective to improve students’ ability in using passive voice. This research used quantitative approach. This is an experimental research with two different classes taught using two different techniques as experiment class and control class. The population of this research was two classes of the eleventh grade students of SMA Global Madani Bandar Lampung. The instrument of this research was a test which was divided into pre-test and post-test. In analyzing the data, it showed that the average score of the pre-test and post-test of experimental class improved from 65.5 for pre-test to 82.9 for post-test. It also showed that showed that the experimental class had a significance value (2-tailed) that was 0.000 (p < 0.05). Therefore, it is concluded that jigsaw techniques has significant effect on teaching passive voice. The result also suggest that the jigsaw reading used in teaching passive voice can be promoted.